Socio-Agricultural Correlation and Regionalization: A Case of the Districts of Pakistan - Razzaq Ahmed; Khalida Mahmood; Anila Kausar (Journal of Basic & Applied Sciences, 2021)
The main economic activity of a large segment of population in Pakistan is agriculture. The contrasting pattern of topography and uneven distribution of resources create a wide difference in socio-agricultural relationship among the different administrative districts of the country. The study aims to investigate the correlation based on a number of variables extracted from different sectors of Pakistan’s agriculture and social infrastructure. In order to study the regionalization multivariate analysis has been done for hundred districts of Pakistan. The results produced, show sharp variation of regional disparity among the different districts of Pakistan. A clear cut longitudinal east-west divide is visible from the outcome of the study. The provinces of Punjab and Sindh, consisting of fertile plains of river Indus and its tributaries stand out with better socio-agricultural correlation. The western provinces of Khyber Pakhtoonkhwa and Balochistan, surrounded by mountains and plateau depict a deprived scene in terms of socio-agricultural well-being. In Pakistan districts are very vital for resource planning and development. These administrative units have a mix of both rural and urban activities that is why this study becomes more significant for future district planning decisions.